Shape-Adaptive Universal Soft Parallel Gripper for Delicate Grasping Using a Stiffness-Variable Composite Structure - Lee, Jae Young; Seo, Yong Sin; Park, Chanhun; Koh, Je Sung; Kim, Uikyum; Park, Jongwoo; Rodrigue, Hugo; Kim, Byeungin; Song, Sung Hyuk (IEEE Transactions on Industrial Electronics, 2021)
The robotic gripper is an essential component for handling, manipulating, and transporting objects. However, the parallel rigid gripper, which is one of the most widely used grippers in robotics, has limitations in handling fragile objects with a proper gripping force. We present a shape-adaptive universal soft gripper that can grip complex-shaped fragile objects with a high holding force. The shape-adaptive skin of the gripper has extremely low stiffness ($\sim$46 kPa), even lower than that of tofu ($\sim$57 kPa); hence, it can inherently prevent damage to the object. In addition, only the area pressed by the object is selectively deformed, so the contact surface of the gripper can be deformed to match the target object contour. A stiffness transition in the gripper from a soft to hard state follows to achieve effective holding of the object, not just weak object hanging as the previous soft gripper. These characteristics are enabled by a sheet-shaped shape retention layer, a honeycomb-shaped soft supporting layer, and a four-sided wall structure to increase shear modulus. We present applications to show the performance of the gripper, including gripping tofu, preparing a cocktail with a squeezed lemon, and whole chicken soup.
Keywords: Contact surface; Fragile objects; Gripping force; Holding forces; Robotic grippers; Shape retention; Shape-adaptive; Wall structure; Shape-adaptive structure; soft robotics; stiffness-variable composite; universal parallel gripper